EFFECT OF MUSIC ON HUMAN BEHAVIOR - Guerrero Viltres, Maydolis; Lebrigio Galafet, Yoandris Orlando; Mendoza Vázquez, Milaidys (Revista Eletrónica KULONGESA – TES. ISSN 2707-353X, 2020)
Musical art is revealed as a eminently social discipline, thus it has been created throughout history, its created by and for groups of people who assume diferente social roles in its relationship with music.The purpose of this work is to reflect on the benefits that music brings to human health. Music helps patients in regaining control over their walking pace after suffering a Traumatic Brain Injury(TBI) it also helps to stimulate the retograde and the anterograde memory,it helps with self esteem, stimulates to create new social relations and it can be used as a contact with reality.